RSV replication modifies the XBP1s binding complex on the IRF1 upstream enhancer to potentiate the mucosal anti-viral response - Qiao, Dianhua; Xu, Xiaofang; Zhang, Yueqing; Yang, Jun; Brasier, Allan R. (Frontiers in Immunology, 2023)
The unfolded protein response (UPR) has emerged as an important signaling pathway mediating anti-viral defenses to Respiratory Syncytial Virus (RSV) infection. Earlier we found that RSV replication predominantly activates the evolutionarily conserved Inositol Requiring Enzyme 1(IRE1-X-Box Binding Protein 1 spliced (XBP1s) arm of the Unfolded Protein Response (UPR) producing inflammation, metabolic adaptation and cellular plasticity, yet the mechanisms how the UPR potentiates inflammation are not well understood. In this manuscript, we observe complex interactions between the IRE1-XBP1s pathway, RSV replication and the cellular innate response. To understand this process better, we examined the genomic response integrating RNA-seq and Cleavage Under Targets and Release Using Nuclease (CUT&RUN) analyses. RNA-seq was conducted on RSV-infected small airway cells where we identified expression changes in ~3.2K genes; of these, 279 required IRE1 and were enriched in IL-10/cytokine signaling pathways. From this data set, we identify those genes directly under XBP1s control by CUT&RUN, Although XBP1s binds to ~4.2 K high-confidence genomic binding sites, surprisingly these sites map to only a small subset of IL10/cytokine signaling genes. We further apply CUT&RUN to find that RSV infection enhances XBP1s loading on 786 genomic sites enriched in AP1/Fra-1, RELA and SP1 binding sites. Within these are a subset of cytokine regulatory factor genes including IFN response factor 1 (IRF1), CSF2, NFKB1A and DUSP10. Focusing on the downstream role of IRF1, selective knockdown (KD) and overexpression experiments demonstrate IRF1 induction controls type I and -III interferon (IFN) and IFN-stimulated gene (ISG) expression, demonstrating that ISG are indirectly regulated by XBP1 through IRF1 transactivation. Examining the mechanism of IRF1 activation, we observe that XBP1s directly binds a 5’ enhancer sequence whose loading is increased by RSV. The functional requirement for the enhancer is demonstrated by targeting a dCas9-KRAB silencer, reducing IRF1 activation. Chromatin immunoprecipitation shows that XBP1 is required, but not sufficient, for RSV-induced recruitment of activated phospho-Ser2 Pol II to the enhancer. We conclude that RSV modulates the XBP1s binding complex on the IRF1 5’ enhancer that activates downstream ISGs. These findings provide novel insight into how the IRE1-XBP1s pathway potentiates airway mucosal anti-viral responses.